(untitled) (Journal of Parents and Teachers, 2014)
Parting from the interindividual differences found in the classrooms, and working with the Multiple Inteligences Theory by Gardner. The need for a qualitative change in the educational system is considered. Envolving from a point of uniformity, to the latest concepts that take into account skills and abilities beyond the traditional ones. Provided with special importance is the “Executive Inteligence” which is understood as optimizer of all th others. Concretly we will be talking about the fundamental learning difficulties of childs that are affected by ADHD, detected mainly in the developement of their “Executive Inteligence”. Therefore, it is concluded that we must include, because of its relevance, a sepecific approach of this “Inteligence or Cognitive Ability” whithin the educatonal system.